The potential effects of introducing microneedle patch vaccines into routine vaccine supply chains. Issue 4 (21st January 2019) - Wedlock, Patrick T.; Mitgang, Elizabeth A.; Elsheikh, Fayad; Leonard, Jim; Bakal, Jenn; Welling, Joel; Crawford, Jessica; Assy, Emmanuelle; Magadzire, Bvudzai P.; Bechtel, Ruth; DePasse, Jay V.; Siegmund, Sheryl S.; et al.
Abstract: Background: Microneedle patch (MNP) technology is designed to simplify the process of vaccine administration; however, depending on its characteristics, MNP technology may provide additional benefits beyond the point-of-use, particularly for vaccine supply chains. Methods: Using the HERMES modeling software, we examined replacing four routine vaccines – Measles-containing vaccine (MCV), Tetanus toxoid (TT), Rotavirus (Rota) and Pentavalent (Penta) – with MNP versions in the routine vaccine supply chains of Benin, Bihar (India), and Mozambique. Results: Replacing MCV with an MNP (5 cm 3 -per-dose, 2-month thermostability, current single-dose price-per-dose) improved MCV availability by 13%, 1% and 6% in Benin, Bihar and Mozambique, respectively, and total vaccine availability by 1% in Benin and Mozambique, while increasing the total cost per dose administered by 0.07 in Benin, 0.56 in Bihar and 0.11 in Mozambique. Replacing TT with an MNP improved TT and total vaccine availability (3% and <1%) in Mozambique only, when the patch was 5 cm 3 and 2-months thermostable but increased total cost per dose administered by 0.14. Replacing Rota with an MNP (at 5–15 cm 3 -per-dose, 1–2 month thermostable) improved Rota and total vaccine availability, but only improved Rota vaccine availability in Bihar (at 5 cm 3, 1–2 months thermostable), while decreasing total vaccine availability by 1%. Finally, replacing Penta with an MNP (at 5 cm 3, 2-months thermostable) improved Penta vaccine availability by 1–8% and total availability by <1–9%. Conclusions: An MNP for MCV, TT, Rota, or Penta would need to have a smaller or equal volume-per-dose than existing vaccine formulations and be able to be stored outside the cold chain for a continuous period of at least two months to provide additional benefits to all three supply chains under modeled conditions.